2017
DOI: 10.1186/s12957-017-1115-6
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral ovarian micrometastatic adenocarcinoma upon prophylactic oophorectomy concurrent with low anterior resection for rectal cancer

Abstract: BackgroundThis case report draws attention to the debated role of prophylactic oophorectomy in women undergoing definitive surgical resection of colon and rectal cancers. It can be challenging to discern the indications and appropriate patient population for this procedure based on the current literature. Potential benefits include treatment and prevention of metastatic disease, preventing development of primary ovarian cancer, and prolonging survival. Negative effects include an increase in operative time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…As a result, POI may result in an earlier onset of osteoporosis 23 . Furthermore, loss of ovarian function due to ovarian removal or cancer chemotherapy can result in the onset of osteoporosis at a young age 24 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, POI may result in an earlier onset of osteoporosis 23 . Furthermore, loss of ovarian function due to ovarian removal or cancer chemotherapy can result in the onset of osteoporosis at a young age 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that ovary removal in women below the age of 45 appears to have an increased mortality risk compared to those above this age [57]. Many negative consequences can, however, largely be prevented by the use of hormone replacement therapy (HRT), which is advised in these specific situations [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…However, current studies are insu cient to identify with this hypothesis. Robin Irons and colleagues reported a retrospective case showing that prophylactic oophorectomy have possible bene ts from rendering them free of suffering metsatasis [17]. Liu et al showed that CRC patients with prophylactic ovariectomy combined with N3 lymph node dissection have good oncological results [18].…”
Section: Discussionmentioning
confidence: 99%